Transition radiation on a superlattice in finite thickness plate generated by two acoustic waves; Journal of Instrumentation; Vol. 13 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-17) - Mkrtchyan A. R. Alpik Rafaelovich (2018, 2018)
Title screen